Case Study: Disseminated intravascular coagulation at autopsy of a child with severe burns resulting in death - Arrozhi, Muhammad Yusuf; Suriyanto, Rusyad Adi; Widagdo, Hendro (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2023)
Childhood is a time of growth and development, both intellectually and emotionally. The Indonesian Child Protection Commission has observed a growing number of cases of violence against children, including physical and verbal abuse, which require special attention and handling. Physical violence can include burns, which are particularly dangerous in developing countries, where the mortality rate is high. Severe burns can result in inhalation injury and sepsis, which can cause coagulation disorders, making it easier for Disseminated Intravascular Coagulation (DIC) to occur. This study aims to describe the coagulation function of severely burnt patients, investigate the potential causes of DIC, and examine other clinical data. The study used a case study approach, analyzing the corpse of a child who suffered from severe burns. An autopsy was performed and supporting examinations were conducted to determine the cause of death. The examination of the patient's laboratory results, treatment records, corpse, and anatomical pathology revealed the presence of DIC. The autopsy of the child's corpse showed severe burns, pale coloring in the tissues under the nails, and blood clots in the epidural, left ventricle, right ventricle, and veins. The cause of death was determined to be severe burns causing multiple organ dysfunction.